Remote sensing across scales and platforms: monitoring Castelporziano nature reserve forest insect outbreaks - Beatrice Petti; Giovanni D’Amico; Cesar Alvites; Francesco Parisi; Emma Bambagioni; Roberta Bruno; Giovanni Santopuoli; Bruno Lassere; Gherardo Chirici; Marco Ottaviano; Marco Marchetti; Saverio Francini (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Predicting Aberrant Fc-fusion Protein Pharmacokinetics from In Silico Structural Properties and Physiologically Based Pharmacokinetic (PBPK) Modeling - Danilo Tomasoni; Alessio Paris; Roberto Visintainer; Kevin D. Cook; Aochiu Chen; Isabel Figueroa; Veena A. Thomas; Luca Marchetti (The AAPS Journal, 2026)
The fusion of therapeutic proteins to the Fc domain of monoclonal antibodies (mAbs) generally improves the proteins' pharmacokinetic (PK) characteristics, extending in vivo half-lives due to the binding of the Fc domain to the FcRn receptor. Yet, several of these Fc-fusion biologics have been observed to have unexpected rapid clearance associated with non-specific off-target binding. Variability in non-specific clearance is often challenging to predict, not well understood, and ultimately can delay the drug development process. In this investigation, we present a computational approach leveraging in silico protein structural properties to extend a physiologically based pharmacokinetic (PBPK) model of mAbs validated on in vivo plasma PK profiles in mice. Selected model parameters affecting protein half-life have been scaled by analytical functions of a panel of calculated in silico protein properties identified by a novel and ad hoc symbolic regression procedure. The resulting extended model has been successfully validated against an independent set of protein plasma PKs, indicating that it can generalize to novel biologics of the same class. Moreover, the extended PBPK model has a median absolute average fold error (AAFE) of 1.18 (min = 1.09; max = 1.51), where values less than 2 typically indicate a good fit. The results enable the de-risking of aberrant PK behaviors, ultimately leading to the selection of Fc-fusion proteins with increased therapeutic value for patients.

Hyperspectral optical signatures of iron‐limitation in a coastal upwelling system - Sacchidanandan V. Pillai; Yayla Sezginer; Adrian Marchetti; Claire P. Till; Emily V. Speciale; Philippe D. Tortell (Limnology and Oceanography, 2026)
Iron‐limitation within the California Current System drives changes in phytoplankton taxonomic composition and photo‐physiology over a range of spatial scales. Here we demonstrate how these iron‐dependent signatures can be resolved, with high spatial resolution, using continuous ship‐board optical measurements. Deck‐board incubation experiments, along with discrete measurements of iron and macro nutrient concentrations and molecular diagnostic signatures, demonstrated contrasting levels of iron stress across our study region in the northern California Current System during summer, 2023. Photosynthetic pigment measurements indicated that phytoplankton assemblages were largely dominated by diatoms, but low and high iron waters contained differing relative abundances of phytoplankton genera with different mean cell sizes. High frequency ship‐board measurements of hyperspectral particulate absorption demonstrated the presence of two optically distinct phytoplankton assemblages that were associated with varying levels of iron stress. The distribution of the optical clusters across the cruise track showed strong coherence with a number of oceanographic and physiological variables, including phytoplankton size, nutrient drawdown ratios, photosynthetic efficiency () and absorption cross‐section (), and maximum photosynthetic rates. Notably, optical signatures explained more of the observed photo‐physiological variability than other oceanographic variables, such as sea surface temperature and chlorophyll concentration. Variability in phytoplankton iron stress appeared coupled to the age and source of the upwelling water masses. Our results demonstrate the utility of hyperspectral data to map potential iron‐stress with high spatial resolution in dynamic coastal waters.

Long-term forestation-deforestation dynamics in a socioeconomic perspective: The case of Italy, 1936–2018 - Alessia D'Agata; Marco Marchetti; Luca Salvati; Piermaria Corona (Forest Policy and Economics, 2025)

Thermochemical processing of organic wastes for sustainable valorisation and energy recovery: A review of recent contributions to the field - Cigdem Yangin-Gomec; Kenan Dalkılıç; Altunay Perendeci; Mine Güngörmüşler; Tosin Somorin; Jimmy Roussel; Murat Varol; Ana Ramos; Eric D. van Hullebusch; Anna Trubetskaya; Feyza Kazanc; Milica Vasić; et al. (Biomass and Bioenergy, 2025)

P09-36 The toxicological effects of ultrafine particles (UFP) resulting from the combustion of fossil-based fuels and bio-fuels in an atmospheric simulation chamber - S. Marchetti; G. Motta; V. Vernocchi; G. De Falco; M. Commodo; A. D'Anna; T. Isolabella; D. Massabò; P. Minutolo; P. Prati; P. Mantecca; M. Gualtieri (Toxicology Letters, 2025)

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Predicting invasiveness of freshwater fishes imported into North America: regional differences in models and outcomes - Jennifer G. Howeth; Sarah A. Amjad; Crysta A. Gantz; Nicholas E. Mandrak; Paul L. Angermeier; Michael P. Marchetti; Julian D. Olden; David M. Lodge (Biological Invasions, 2025)
Biological invasions driven by international trade heighten the urgency for development of invasion risk models, as the traits and parameters that consistently predict successful invasion remain unresolved. For four regions of North America that include parts of the United States and Canada (Sacramento-San Joaquin River Basins, Lower Colorado River Basin, Great Lakes Region, Mid-Atlantic Region), we construct and compare classification tree models to reveal robust predictors for the establishment and ecological impact stages of freshwater fish invasion. We subsequently apply the models to identify invasive fish species in trade and conduct pathway analyses to determine which trades (aquarium, biological supply, live bait, live food, water garden) and source continents pose the greatest risk to each region. Model results differed by invasion stage and region. Across regions, establishment models shared climate-related predictors including climate match and temperature tolerance. Three of the four impact models contained prior establishment success. The greatest number of species (548) were predicted to establish in the Sacramento-San Joaquin while the fewest (5) were predicted to establish in the Mid-Atlantic. Forty species were predicted to establish in multiple regions, five of which were also predicted to have high impact. The aquarium trade and Asia supplied the most species predicted to establish. Taken together, the results highlight region-specific models, indicating no universal model predicts invasion. Climate-related and prior establishment variables were most useful to risk assessments. The regional models, and identified high-risk pathways and potential invaders, could be applied to prevent future fish invasions in North America.

Inhalation of nanoplastics in the mouse model: Tissue bio-distribution and effects on the olfactory system - G. Prosperi; N. Marchetti; A. D'Elia; R. Massari; M. Giusto; A. Pietrodangelo; T. Rossi; A. Nucara; F. Scavizzi; G. Strimpakos; S. Marinelli; S. Mandillo; et al. (Science of The Total Environment, 2025)

The impact of the spatial resolution of vegetation cover on the prediction of airborne pollen concentrations over northern Italy - Sofia Tagliaferro; Mario Adani; Nicola Pepe; Gino Briganti; Massimo D'Isidoro; Maira Bonini; Antonio Piersanti; Sandro Finardi; Pierpaolo Marchetti; Francesco Domenichini; Mihaela Mircea; Maria Gabriella Villani; et al. (Agricultural and Forest Meteorology, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Concentration of polycyclic aromatic hydrocarbons (PAHs) and histological changes in Anomalocardia brasiliana and Crassostrea rhizophorae from Pernambuco, Brazil after the 2019 oil spill - Gisely Karla de Almeida Costa; Scarlatt Paloma Alves da Silva; Maria Raissa Coelho Marchetti Trindade; Fernando Leandro dos Santos; Renato S. Carreira; Carlos G. Massone; Otoniel D. Sant'Ana; Suzianny Maria Bezerra Cabral da Silva (Marine Pollution Bulletin, 2023)

Error-corrected duplex sequencing enables direct detection and quantification of mutations in human TK6 cells with strong inter-laboratory consistency - Eunnara Cho; Carol D. Swartz; Andrew Williams; Miriam V. Rivas; Leslie Recio; Kristine L. Witt; Elizabeth K. Schmidt; Jeffry Yaplee; Thomas H. Smith; Phu Van; Fang Yin Lo; Charles C. Valentine; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

The erythrocyte sedimentation rate (ESR) in canine inflammation - E. Gori; A. Pierini; A. Pasquini; D. Diamanti; C. Carletti; G. Lubas; V. Marchetti (The Veterinary Journal, 2023)

Large-scale high-resolution yearly modeling of forest growing stock volume and above-ground carbon pool - Elia Vangi; Giovanni D'Amico; Saverio Francini; Costanza Borghi; Francesca Giannetti; Piermaria Corona; Marco Marchetti; Davide Travaglini; Guido Pellis; Marina Vitullo; Gherardo Chirici (Environmental Modelling & Software, 2023)

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Population Pharmacokinetics of Intracellular 5-Fluorouridine 5′-Triphosphate and its Relationship with Hand-and-Foot Syndrome in Patients Treated with Capecitabine - Julie M. Janssen; Bart A. W. Jacobs; Jeroen Roosendaal; Ellen J. B. Derissen; Serena Marchetti; Jos H. Beijnen; Alwin D. R. Huitema; Thomas P. C. Dorlo (The AAPS Journal, 2021)

Antifungal activity of oils macerates of North Sardinia plants against Candida species isolated from clinical patients with candidiasis - M.G. Donadu; D. Usai; M. Marchetti; M. Usai; V. Mazzarello; P. Molicotti; M.A. Montesu; G. Delogu; S. Zanetti (Natural Product Research, 2020)

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

Interannual radial growth sensitivity to climatic variations and extreme events in mixed-species and pure forest stands of silver fir and European beech in the Italian Peninsula - S. Versace; D. Gianelle; V. Garfì; G. Battipaglia; F. Lombardi; M. Marchetti; R. Tognetti (European Journal of Forest Research, 2020)

Phase I pharmacological study of continuous chronomodulated capecitabine treatment - Jeroen Roosendaal; Bart A. W. Jacobs; Dick Pluim; Hilde Rosing; Niels de Vries; Erik van Werkhoven; Bastiaan Nuijen; Jos H. Beijnen; Alwin D. R. Huitema; Jan H. M. Schellens; Serena Marchetti (Pharmaceutical Research, 2020)
Purpose Capecitabine is an oral pre-pro-drug of the anti-cancer drug 5-fluorouracil (5-FU). The biological activity of the 5-FU degrading enzyme, dihydropyrimidine dehydrogenase (DPD), and the target enzyme thymidylate synthase (TS), are subject to circadian rhythmicity in healthy volunteers. The aim of this study was to determine the maximum tolerated dose (MTD), dose-limiting toxicity (DLT), safety, pharmacokinetics (PK) and pharmacodynamics (PD) of capecitabine therapy adapted to this circadian rhythm (chronomodulated therapy). Methods Patients aged ≥18 years with advanced solid tumours potentially benefitting from capecitabine therapy were enrolled. A classical dose escalation 3 + 3 design was applied. Capecitabine was administered daily without interruptions. The daily dose was divided in morning and evening doses that were administered at 9:00 h and 24:00 h, respectively. The ratio of the morning to the evening dose was 3:5 (morning: evening). PK and PD were examined on treatment days 7 and 8. Results A total of 25 patients were enrolled. The MTD of continuous chronomodulated capecitabine therapy was established at 750/1250 mg/m 2 /day, and was generally well tolerated. Circadian rhythmicity in the plasma PK of capecitabine, dFCR, dFUR and 5-FU was not demonstrated. TS activity was induced and DPD activity demonstrated circadian rhythmicity during capecitabine treatment. Conclusion The MTD of continuous chronomodulated capecitabine treatment allows for a 20% higher dose intensity compared to the approved regimen (1250 mg/m 2 bi-daily on day 1–14 of every 21-day cycle). Chronomodulated treatment with capecitabine is promising and could lead to improved tolerability and efficacy of capecitabine.

Magnetic Field and Electron Density Anomalies from Swarm Satellites Preceding the Major Earthquakes of the 2016–2017 Amatrice-Norcia (Central Italy) Seismic Sequence - Dedalo Marchetti; Angelo De Santis; Serena D’Arcangelo; Federica Poggio; Shuanggen Jin; Alessandro Piscini; Saioa A. Campuzano (Pure and Applied Geophysics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Remote Sensing for Maritime Prompt Monitoring - Marco Reggiannini; Marco Righi; Marco Tampucci; Angelica Lo Duca; Clara Bacciu; Luigi Bedini; Andrea D’Errico; Claudio Di Paola; Andrea Marchetti; Massimo Martinelli; Costanzo Mercurio; Emanuele Salerno; et al. (Journal of Marine Science and Engineering, 2019)
The main purpose of this paper is to describe a software platform dedicated to sea surveillance, capable of detecting and identifying illegal maritime traffic. This platform results from the cascade pipeline of several image processing algorithms that input Radar or Optical imagery captured by satellite-borne sensors and try to identify vessel targets in the scene and provide quantitative descriptors about their shape and motion. This platform is innovative since it integrates in its architecture heterogeneous data and data processing solutions with the goal of identifying navigating vessels in a unique and completely automatic processing streamline. More in detail, the processing chain consists of: (i) the detection of target vessels in an input map; (ii) the estimation of each vessel’s most descriptive geometrical and scatterometric (for radar images) features; (iii) the estimation of the kinematics of each vessel; (iv) the prediction of each vessel’s forthcoming route; and (v) the visualization of the results in a dedicated webGIS interface. The resulting platform represents a novel tool to counteract unauthorized fishing and tackle irregular migration and the related smuggling activities.

Peripheral and cerebrospinal fluid immune activation and inflammation in chronically HIV-infected patients before and after virally suppressive combination antiretroviral therapy (cART) - E. Merlini; F. Iannuzzi; A. Calcagno; F. Bai; M. Trunfio; A. d’Arminio Monforte; S. Bonora; Giulia Marchetti (Journal of NeuroVirology, 2018)

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Symbiodinium Functional Diversity in the Coral Siderastrea siderea Is Influenced by Thermal Stress and Reef Environment, but Not Ocean Acidification - Sarah W. Davies; Justin B. Ries; Adrian Marchetti; Karl D. Castillo (Frontiers in Marine Science, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Anthropogenic impact in the Maya Lowlands of Petén, Guatemala, during the last 5500 years - D. Battistel; M. Roman; A. Marchetti; N. M. Kehrwald; M. Radaelli; E. Balliana; G. Toscano; C. Barbante (Journal of Quaternary Science, 2018)
Trace and rare earth elements from a sediment core from Lake Petén Itzá (Guatemala) depict the geochemical dynamics affecting the lake from ∼5500 a BP to the present. This timing encompasses the Preclassic (4000–1700 a BP) and Classic Periods (1700−1000 a BP) when thriving Maya societies extensively cleared land for agriculture. We demonstrate that this land use occurred during times of increased precipitation, where both processes resulted in increased erosion. Rare earth element ratios depict high precipitation rates between 3000 and 1000 a BP, correlating with an increase in allochthonous silicate input and low organic carbon in the ‘Maya Clay’ stratigraphic section, where this layer is ascribed to intensive anthropogenic land use. Cesium anomalies provide additional evidence for runoff due to high rainfalls and amplified by anthropogenic impacts. The Petén Itzá core contains anomalous spikes of arsenic and mercury, and these peaks correspond to documented volcanic eruptions and therefore are probably natural. The geochemical composition of sediments and palynological records indicate re‐growth of the forest after ∼900 a BP. This increased forest vegetation coincides with the timing of the decline in Maya agriculture.

Space-Wise approach for airborne gravity data modelling - D. Sampietro; M. Capponi; A. H. Mansi; A. Gatti; P. Marchetti; F. Sansò (Journal of Geodesy, 2017)

The influence of slope on Spartium junceum root system: morphological, anatomical and biomechanical adaptation - Fabio Lombardi; G. S. Scippa; B. Lasserre; A. Montagnoli; R. Tognetti; M. Marchetti; D. Chiatante (Journal of Plant Research, 2017)

GTE: a new software for gravitational terrain effect computation: theory and performances - D. Sampietro; M. Capponi; D. Triglione; A. H. Mansi; P. Marchetti; F. Sansò (Pure and Applied Geophysics, 2016)

Streptococcus salivarius by nasal spray for recurrent otitis: how good is the evidence? - S. Di Mario; V. Basevi; R. D’Amico; C. Gagliotti; M. Gangemi; F. Marchetti; M. L. Moro; G. Tamburlini (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Thermal and pCO2 Stress Elicit Divergent Transcriptomic Responses in a Resilient Coral - Sarah W. Davies; Adrian Marchetti; Justin B. Ries; Karl D. Castillo (Frontiers in Marine Science, 2016)

First mapping of the main high conservation value forests (HCVFs) at national scale: The case of Italy - M. Maesano; B. Lasserre; M. Masiero; D. Tonti; M. Marchetti (Plant Biosystems, 2016)

Three new hybrids of Ophioglossum (Ophioglossaceae) from Monte Pisano, Tuscany (Central Italy) - L. Peruzzi; B. Pierini; S. Magrini; A. Andreucci; D. Marchetti; R. Viane (Plant Biosystems, 2015)

Implementing REDD+ in Papua New Guinea: Can biodiversity indicators be effectively integrated in PNG's National Forest Inventory? - G. Grussu; F. Attorre; D. Mollicone; P. Dargusch; A. Guillet; M. Marchetti (Plant Biosystems, 2014)

Do National Parks play an active role in conserving the natural capital of Italy? - G. Capotorti; L. Zavattero; I. Anzellotti; S. Burrascano; R. Frondoni; M. Marchetti; M. Marignani; D. Smiraglia; C. Blasi (Plant Biosystems, 2012)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Linking taxonomical and functional biodiversity of saproxylic fungi and beetles in broad‐leaved forests in southern Italy with varying management histories - A. M. Persiani; P. Audisio; D. Lunghini; O. Maggi; V. M. Granito; A. B. Biscaccianti; U. Chiavetta; M. Marchetti (Plant Biosystems, 2010)

ForestBIOTA data on deadwood monitoring in Europe - D. Travaglini; A. Barbati; G. Chirici; F. Lombardi; M. Marchetti; P. Corona (Plant Biosystems, 2007)

The awareness among paediatricians of off-label prescribing in children: a survey of Italian hospitals - Federico Marchetti; Jenny Bua; Alessandro Ventura; Luigi D. Notarangelo; Salvatore Di Maio; Giuseppina Migliore; Maurizio Bonati (European Journal of Clinical Pharmacology, 2007)

Cultural heritage and geological hazards: the case of the Calomini hermitage in Tuscany (Italy) - Giacomo D’Amato Avanzi; Daria Marchetti; Alberto Puccinelli (Landslides, 2006)

Histology and carbohydrate histochemistry of the alimentary canal in the rainbow trout Oncorhynchus mykiss - L. Marchetti; M. Capacchietti; M. G. Sabbieti; D. Accili; G. Materazzi; G. Menghi (Journal of Fish Biology, 2006)
A histological and histochemical analyses were carried out on the entire alimentary canal of the rainbow trout Oncorhynchus mykiss . In particular the oesophageal region showed presence of terminal β‐D‐galactose(1–3)‐N‐acetylgalactosamine and α‐N‐acetylgalactosamine. In the anterior and posterior regions of the stomach, lining epithelium and gastric pits exhibited the presence of β‐gal and α‐GalNAc. In addition sialoglycoconjugates having sialic acid–β–galactose(1–3)‐N‐acetylgalactosamine and sialic acid‐N‐acetylgalactosamine as terminal tri‐ and di‐saccharides, were demonstrated. In proximal and distal intestine goblet cells showed the presence of sialoglyconjugates, having sialic acid‐β‐gal(1–3)‐GalNAc and sialic acid‐GalNAc as terminal sequences, belonging to N‐linked chains. In the enterocytes of the entire intestine, terminal GlcNAc, α‐Gal, α‐fucose were found.

Heparanase Expression and TrkC/p75NTR Ratios in Human Medulloblastoma - Neeta D. Sinnappah-Kang; Robert E. Mrak; Daniel B. Paulsen; Dario Marchetti (Clinical & Experimental Metastasis, 2006)

Molecular markers linked to the blast resistance gene Pi-z in rice for use in marker-assisted selection - C. A. Conaway-Bormans; M. A. Marchetti; C. W. Johnson; A. M. McClung; W. D. Park (Theoretical and Applied Genetics, 2003)

Mapping of four major rice blast resistance genes from ’Lemont’ and ’Teqing’ and evaluation of their combinatorial effect for field resistance - R. E. Tabien; Z. Li; A. H. Paterson; M. A. Marchetti; J. W. Stansel; S. R. M. Pinson; W. D. Park (Theoretical and Applied Genetics, 2000)

The effect of urea and pig slurry fertilization on denitrification, direct nitrous oxide emission, volatile fatty acids, water-soluble carbon and anthrone-reactive carbon in maize-cropped soil from the Po plain (Modena, Italy) - P. G. Arcara; C. Gamba; D. Bidini; R. Marchetti (Biology and Fertility of Soils, 1999)

Biosynthesis and cytoplasmic accumulation of a chlorinated catechol pigment during 3-chlorobenzoate aerobic co-metabolism in Pseudomonas fluorescens - F. Fava; D. Di Gioia; C. Romagnoli; L. Marchetti; D. Mares (Archives of Microbiology, 1993)